1972
DOI: 10.1063/1.1685599
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Disk Apparatus for Reaction Rate Studies in Corrosive Liquid Environments

Abstract: This paper describes the design and use of a rotating disk apparatus for studying reactions between fluids and solid surfaces. The apparatus is capable of operation in extremely corrosive liquid environments under controlled pressures and temperatures up to 70 atm and 150°C. The design includes a unique magnetic drive assembly that allows the disk to be rotated in the high pressure reactor vessel without the need of a stuffing box seal. All parts that contact corrosive fluids are fabricated from Hastelloy allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…and the diffusion boundary layer thickness is [18] 1/3 / \ 1/2 6 rf s 1.611-It has also been reported that to safely maintain laminar conditions in a rotating disk Re should be less than 1.9 x 10 5 [19]. The diffusion boundary layer, 8 d , plays an important role in the transport behavior for fluid flows involving concentration gradients of chemical species.…”
Section: Experimental Verificationmentioning
confidence: 97%
“…and the diffusion boundary layer thickness is [18] 1/3 / \ 1/2 6 rf s 1.611-It has also been reported that to safely maintain laminar conditions in a rotating disk Re should be less than 1.9 x 10 5 [19]. The diffusion boundary layer, 8 d , plays an important role in the transport behavior for fluid flows involving concentration gradients of chemical species.…”
Section: Experimental Verificationmentioning
confidence: 97%
“…This instrument has been extensively used to investigate the reaction of acids and chelating agents with carbonate rocks. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been also used to study mass and heat transfer into non-Newtonian fluids. [16][17][18] The reaction between acid and rock is a three-step process involving:…”
Section: Introductionmentioning
confidence: 99%
“…Between 100 and 2000 rpm is the rotating speed range of this rotating reactor. Boomer & McCune (1972) designed and used a rotating disk apparatus for studying the reaction between calcium carbonate disks and hydrochloric acid. This apparatus can be operated in enormously corrosive liquid environments under controlled pressures and temperatures up to 70 atm and 150 o C. The calcium carbonate disks were cut from a white Vermont marble (analyzed as 98-99% calcium carbonate) with 5.1 cm in diameter and 0.64 cm thickness.…”
Section: Rotating Disk Reactormentioning
confidence: 99%
“…The rotating disk instrument is increasingly being applied in the laboratory to study the reaction between fluids and solid surfaces. It is widely used in the petroleum industry for kinetic studies of the reaction of acidic fluids and chelating agents with reactive rock (Boomer, Mccune & Fogler, 1972;Fredd & Fogler, 1998;K. Lund, Fogler & Mccune, 1973;K.…”
Section: Introductionmentioning
confidence: 99%